The Effect of Digital Marketing and Service Quality on Sales Volume of Wiego Houseware Medan Marelan in Facing Technology Challenges - Desma Erica Maryati Manik; Eric Angkasa (CV. Ulil Albab Corp, 2025)
The purpose of this study was to determine the effect of digital marketing and service quality on sales volume at Wiego Houseware Marelan. This research was conducted from July 2024 to November 2024. This type of research uses quantitative research, the data source in this study is primary. The population in this study were customers who made purchases of more than Rp. 100,000,000, - at Wiego Houseware in 2023 as many as 184 customers. The sample of this study were retail stores that made purchases in 2023 totaling 126 stores obtained using the slovin formula with a 5% error percentage. Data collection techniques through questionnaires using Likert scale measurements. The results showed that the Digital Marketing variable (X1) had a partially significant effect on sales volume. Service Quality (X2) has a partially significant effect on sales volume. Digital Marketing (X1) Service Quality (X2) has a significant effect simultaneously on sales volume and a regression coefficient value of 75.4%.